IMPLEMENTASI PERATURAN DAERAH KOTA PALANGKA RAYA NOMOR 22 TAHUN 2014 TENTANG RETRIBUSI PELAYANAN PERSAMPAHAN/KEBERSIHAN (Studi Terhadap Pedagang Kreatif Lapangan Dalam Pelaksanaan Car Free Day di Bundaran Besar Kota Palangka Raya) - Eriani; Ira Zuraida; Suprayitno (Journal Ilmu Sosial, Politik dan Pemerintahan, 2019)
Cleanliness Retribution is one of the sources that has the potential to increase Regional Original Income, especially in the implementation of Car Free Day in the “Bundaran Besar” Palangka Raya City. This can be seen from its contribution to the Regional Original Income which is quite large and always increases every year. This cleanliness levy serves to fulfill the routine needs of the regional treasury, regulate the health of the community and the environment, as well as to cover the costs of administering waste / cleaning services. This study aims to find out, analyze and describe how the implementation of Regional Regulations Regarding Cleaning Levies Against Creative Traders of Car Free Day in the “Bundaran Besar” Palangka Raya City. In addition, it is also to analyze the factors that influence the implementation of Regional Regulations concerning Cleaning Levies Against Creative Traders in the Car Free Day “Bundaran Besar” Palangka Raya City. The author uses the theory of policy implementation from George C. Edward III which consists of four indicators, namely communication, resources, disposition and bureaucratic structure. This study uses a Qualitative Approach with data collection techniques that include Observation, Interview and Documentation. From the results of the study, it was found that the Implementation of Regional Regulations concerning Hygiene Levies on Creative Traders of Car Free Day “Bundaran Besar” Palangka Raya City is still not optimal, so it still needs to be addressed.The conclusions from the research on the implementation of the Regional Regulations on Hygiene Levies Against Creative Traders of Car Free Day “Bundaran Besar” Palangka Raya City are still not optimal, this is caused by the first, the lack of supervision by the management agency so that it is prone to irregularities. Secondly, there was no socialization regarding the content and purpose of the Regional Regulations concerning Cleanliness retribution. Third, the management office is less aware of the potential for cleaning fees at the location.